Pengaruh Intensitas Modal, Struktur Modal, Dan Profitabilitas Terhadap Nilai Perusahaan Di Sektor Industri Makanan & Minuman Indonesia Pasca-Covid (2020–2024 - Nurul Fatimah Rachmat; Rima Azhar Fadilah; Nuri Lestari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze the influence of capital intensity, capital structure, and profitability on firm value in the food and beverage subsector in Indonesia during the post-COVID-19 pandemic period (2020–2024). The data used are secondary data from the annual financial reports of eight food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX). The analysis method used is panel data regression with a Random Effect Model (REM) approach using EViews software. The results show that the variables of capital structure (DER), capital intensity (CIR), and profitability (ROE) partially or simultaneously do not have a significant effect on firm value (Tobin's Q). This indicates that during the post-pandemic recovery period, external factors such as macroeconomic conditions, inflation, and fluctuations in raw material prices are more dominant in influencing firm value than internal financial factors. These findings emphasize the importance of strengthening financial strategies and operational efficiency for food and beverage subsector companies to maintain firm value in the post-pandemic era.